ANALISIS STRATEGI PENGEMBANGAN AGRIBISNIS KOMODITAS SAYURAN UNGGULAN DI ASOSIASI ASPAKUSA MAKMUR KABUPATEN BOYOLALI - Agus Prayitno; Suprapti Supardi; Eka Dewi Nurjayanti (MEDIAGRO, 2012)
This research aim to know profile effort and business area, internal factor and eksternal and alternative of association agribusiness strategy Aspakusa Makmur in expansion of pre-eminent vegetable agribusiness. Primary Data and secondary has been analysed to answer purpose of research. Analysis done by using matrik intenal/eksternal and matrik SWOT. Research responder consisted of official member of association, member of association, on duty agriculture and cooperation partner. Result of analysis matrik IFE to degree of importance based on factor wight - internal strategy influence factor at strength aspect of sequentially from a real important is motivation and loyality official member and member (0,18), supporting facilities for infrastructure (0,17), quality of better product (0,15), mission vision and institution of organization (0,13), and produce of vegetable (0,10). The biggest weakness factor associated is capital member of asosiasi/petani binaan terbatas/kecil and cistern of rain conducting system (0,09). Analysis matrik EFE menunjukan environmental factor eksternal which is highest had an effect on to association based on highest wight value successively is geographical position and conducting region (0,20), market opportunity (0,17), support from on duty sub-province agriculture (0,15), free market commerce (0,13), condition of politics social (0,06). The biggest threat factor is existence of competitor with wight value (0,10). Analysis matrik IE, with internal factor score total value 2,88 that contact with factor score total eksternal 3,19 at cell to 2 from 9 strategy cell. Alternative of strategy which can be done is increase product vegetable with quality, extends marketing, maintains quality of product, farmer access facility to defrayal institute, rekruitmen promotion division, increases quality of packaging, conducting applies greenhouse and net paranet, designs effective training system and studies comparing. Keyword : Aspakusa Makmur, Matrix IFE, Matrix EFE, Matrix SWOT, Agribusiness Strategy